Kejahatan Genosida dan Hukum Internasional: Analisis Peran Icc dan Hambatan Yang Dihadapi dalam Penegakan Keadilan - Nike Cahyaningrum; Wardah Apriani; Rahma Syifa Az Zahra; Clarissa Adinda Intan Artamevia; Nysa Amalia (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Genocide is one of the most serious crimes in international law, regulated by various legal instruments such as the 1948 Genocide Convention and the 1998 Rome Statute. This crime involves the intent to destroy, in whole or in part, a group based on race, ethnicity, religion, or nationality. This study aims to analyze the role of the International Criminal Court (ICC) in enforcing genocide law and identify the obstacles in applying individual criminal responsibility. Additionally, mechanisms for resolving genocide disputes through peaceful and legal means in international law are discussed. The research employs a qualitative approach with a descriptive-analytical method, analyzing international legal documents and case studies. The results show that although the ICC has jurisdiction to try genocide cases, law enforcement processes often face political challenges, particularly the UN Security Council veto power and state sovereignty. In conclusion, international efforts to address genocide require stronger cross-country cooperation and enhanced legal mechanisms to overcome political and diplomatic challenges.